Propuesta de mejoramiento de la productividad a partir de la redistribución de planta y herramientas Lean Manufacturing en la empresa Maderpaco - Rodríguez Castro, Santiago Danilo (Universidad Antonio Nariño, 2022)
This research work was carried out in the company MADERPACO, which is dedicated to the manufacture and commercialization of wooden pieces based on three fundamental processes: Machining, Sanding and Assembly. It is a proposal for redistribution in the plant accompanied by Lean Manufacturing tools whose objective is to increase productivity through the optimization of times, routes, movements and use of raw materials. The project begins from an initial diagnosis where the different factors that intervene in the production process were identified, such as: machinery, personnel, raw materials, manufactured products and the procedure for their manufacture. After the diagnosis stage, it is convenient to prepare the diagrams, mainly the current distribution design and the relational diagram by departments, this with the aim of identifying the degree of closeness necessary between the work areas, later a study was established of times by means of course charts in order to establish the cycle times and the movements carried out. Next, a proposal was selected through a cost-benefit analysis adding the 5's methodology to correct the deficiencies and problems found throughout the study. In summary, through the implementation of the redistribution proposal, it is possible to reduce cycle times and routes for the manufacture of the different pieces, its application and monitoring is recommended for continuous improvement.